EXTH-63. LIPOSOMAL DELIVERY OF FERRITIN HEAVY CHAIN (FTH1) siRNA RESULTS IN INCREASED RADIATION SENSITIVITY IN PATIENT DERIVED GLIOMA INITIATING CELLS. (11th November 2019) - Ravi, Vagisha; Abraham, Thomas; Madhankumar, Achuthamangalam; Slagle-Webb, Becky; Pandya, Bhavyata; Connor, James
Abstract: Glioblastoma (GBM) is the most lethal and incurable brain cancer. Despite maximum treatment, high recurrence rates result in median survival of less than 2 years. A subset of treatment resistant cells within GBM known as glioma initiating cells (GICs) are implicated in recurrence and exhibit ferritin overexpression. High expression of ferritin is known to be associated with poor overall survival in GBM patients. Our previous finding showed that downregulation of the ferritin heavy chain subunit (FTH1) enhanced treatment sensitivity in astrocytoma cells. Recently, functional importance of FTH1 in GICs was demonstrated by shRNA silencing leading to ablation of tumorigenic ability. We therefore posited that disrupting iron metabolism through FTH1 knockdown would radiosensitize GICs. Thus we developed multivalent cationic liposomes that enabled delivery of FTH1 siRNA to patient derived GICs isolated from pro-neural (PN) and mesenchymal (Mes) GBM. In both subtypes, FTH1 loss led to increased apoptosis and reduced cell viability. When exposed to radiation, PN GICs were unable to repair and recover from DNA damage, leading to a further decrease in cell viability and a complete loss of reproductive clonogenic potential unlike their more radioresistant Mes counterparts. Moreover, expression of stem cell marker Nestin was markedly reduced in PN but not Mes GICs. Thus, FTH1 loss is detrimental to both GIC subtypes, it seems to be critical for maintaining stemness and radiation resistance of PN GICs. These findings further support the viability of FTH1 as a therapeutic target in GBM.